The impact of 9/11 on muslim identity in the Canadian National Capital Region : institutional response and future prospects.” - Yousif, Ahmad (SAGE, 2005)
Since the destruction of the twin towers in New York City on September 11, 2001, Muslims in the CNCR have been thrust to the forefront of the political scene. The association of this tragedy with Islam and Muslims has put a tremendous amount of pressure on Canadian Muslims and their identity. This paper seeks to determine the extent to which the Muslim community in the CNCR has been able to maintain its religious identification, while at the same time adhere to Canadian social values and lifestyle, particularly in the aftermath of 9/11. It will commence with a general overview of the changing demographic characteristics of the Muslim community in the CNCR. Secondly, the negative and “positive” impacts of 9/11 on Muslims will be assessed. Thirdly, the role-played by Muslim institutions in assisting Muslims to adjust to the crises will be discussed. Finally, recommendations will be made on how Muslims can enhance their acculturation into Canadian society in the aftermath of 9/11, to ensure they remain a vibrant part of the Canadian multicultural mosaic. This study is based primarily on a literature review, sociological observations of the Muslim Community in the CNCR, unstructured field interviews with prominent Muslim leaders and intellectuals, as well as government and non-government social service providers.